Studi Literatur Penerapan Manajemen Risiko Pada Bank Syariah - Utami, Lola Citra; Aqil, Muhammad; Chairina, Chairina (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Despite the fact that Islamic banking has developed significantly to date, business activities and the risks associated with operating financial institutions cannot be separated. When Islamic banking functions as a financial intermediary for Indonesian businesses, there will always be risks. Risk management can measure and mitigate risks to find solutions to problems. At Bank Syariah Indonesia, the implementation of risk management is going well. The implementation of risk management is generally divided into 8, namely: credit risk, liquidity risk, market risk, operational risk, legal risk, compliance risk, reputation risk, strategic risk. The following is the implementation of good risk management: Risk management governance must go through internal control processes and risk management processes. Therefore, Banks must identify and manage risk management inherent in every banking system activity.